Analysis of the Meaning of Da'wah Instagram Account @Muslimahtangguh: Analisis Makna Dakwah Akun Instagram @Muslimahtangguh - Noviatul Ulla (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2021)
Da'wah is an islamic syiar Activity that plays an important role in the spread of islam to all corners of islam to all cornees of the world. The development of the times requires da'wah actors to be able to innovate da'wah, there are many methods used to convey da'wah, one of which is Instagram. This study analyzes posts containing da'wah messages usinh Roland Barthes' Semiotic approach. The purpose of this study is to find out the messages of da'wah contained in the @muslimahtangguh account post.. the type of research is descriptive with a qualitative approach, the type of analysis used ia the semiotic analysis of Roland Barthes, which is to find out what is behind a sihn. Post or uploads on the Instagram account @muslimahtangguh have a denotatibe meaning, namely the meaning of existing culture, and the meaning of myths, things that develop and are contained then associated with Islamic symbols. The @muslimahtangguh account post also contains da'wah messages in the form of creed, sharia, and morals. The @muslimahtangguh account also has a role in conveying da'wah messages and giving readers a unique and interesting da'wah display that contains religious teachings.